2022
DOI: 10.1111/liv.15221
|View full text |Cite
|
Sign up to set email alerts
|

Management of alcohol‐related liver disease: the French Association for the Study of the Liver and the French Alcohol Society clinical guidelines

Abstract: Excessive alcohol consumption is the leading cause of liver diseases in Western countries, especially in France. Alcohol‐related liver disease (ARLD) is an extremely broad context and there remains much to accomplish in terms of identifying patients, improving prognosis and treatment, and standardising practices. The French Association for the Study of the Liver wished to organise guidelines together with the French Alcohol Society in order to summarise the best evidence available about several key clinical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 119 publications
0
10
0
2
Order By: Relevance
“…The GRADE approach not only weighs each recommendation by supporting evidence, but also highlights where the gaps in our understanding remain. For example, since alcohol consumption is often underreported, continuous efforts to uncover the surreptitious harmful alcohol use in the general population are important aspects of all 3 guidelines ( 1 - 3 ). Recent work has suggested that biomarkers of alcohol consumption may be useful in screening the general population.…”
Section: What’s New?mentioning
confidence: 99%
See 2 more Smart Citations
“…The GRADE approach not only weighs each recommendation by supporting evidence, but also highlights where the gaps in our understanding remain. For example, since alcohol consumption is often underreported, continuous efforts to uncover the surreptitious harmful alcohol use in the general population are important aspects of all 3 guidelines ( 1 - 3 ). Recent work has suggested that biomarkers of alcohol consumption may be useful in screening the general population.…”
Section: What’s New?mentioning
confidence: 99%
“…Louvet et al recently published the French Association for the Study of the Liver (AFEF) and the French Alcohol Society clinical guidelines ( 1 ). The AFEF guidelines are the first specific to the screening and care of alcohol-related liver disease (ALD) in France.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Его определение и критерии диагностики усовершенствованы Национальным институтом изучения злоупотребления алкоголем и алкоголизма (National institute on alcohol abuse and alcoholism) в 2016 г. [8], и именно они указаны в клинических рекомендациях большинства стран [9][10][11][12]. АГ называют клиническую форму АБП с быстро развивающейся желтухой и повышением сывороточного уровня аспартатаминотрансферазы (АСТ), возникающими на фоне тяжелого злоупотребления алкоголем [8].…”
Section: алкогольный гепатитunclassified
“…The unbalanced recommendation from France about alcohol-related liver disease claiming that 'The presence of liver disease does not generally affect the prescribing of baclofen at the doses recommended by the marketing authorization' deserved comment when considering the international impact of the Journal. 1 Indeed, baclofen use is off-label, except in France. The French Alcohol Society cannot ignore that the director of the French medicines' agency granted marketing approval despite the Special Scientific Committee concluding that the benefits/harms ratio was negative.…”
mentioning
confidence: 99%